Eliciting web site preferences of people with learning disabilities. Issue 1 (22nd January 2015) - Williams, Peter
Abstract : The Internet can be an excellent tool to help people with learning disabilities access relevant and appropriately written information. However, little work has been undertaken to ascertain web design or content preferences for this cohort. This paper examines methods to address this issue. Twenty five participants were presented with three web sites dealing with employment information. They were asked to browse each and carry out a series of set‐tasks. Interviews and a rating scale ascertained preferences. The problem of acquiescence bias, the tendency for people to automatically agree with those in perceived positions of authority, was minimised by the avoidance of 'polar interrogatives' (questions requiring a 'yes/no' or similarly polarised answer). Participants liked the use of pictures, especially when they featured other young people with learning disabilities. Abstract content related to money or benefits often went unnoticed. Audio was appreciated where offered, although not extensively used. Preferences regarding text size and menu position were also established. Results are compared to other relevant literature and recommendations formulated to help web developers and information providers. The methodological issues inherent in this study were the use of the rating system, and the interview technique. The former was adapted following early findings that the neutral position, on a three point scale, was confusing. Using four points avoided this problem and produced more varied results. Avoiding polar interrogatives greatly helped in minimising 'acquiescence bias'. The study concludes that it is possible to elicit considerable information from people who find it difficult to articulate their views.